Bats - Faisal Ali, Anwarali Khan; Norfarhana, Mazlan; Julius William, Dee; Muhd Amsyari, Morni; Qhairil Shyamri, Rosli; Shafri, Semawi; Mohd Ridwan, Abd Rahman; Roberta Chaya Tawie, Tingga; Mohd Azlan, Jayasilan (UNIMAS Publisher, 2019)
The forests of Santubong National Park include mangroves, mixed-dipterocarp, heath (Kerangas), and hill forests. This complex environment supports a rich bat diversity, as also observed at the nearby Bako National Park and Tanjung Datu National Park. Observing this diversity is sometimes not an easy affair, as the upland areas are challenging for the deployment of traps. The biodiversity enumerated in this chapter is based on trapping effort that focused on the lower parts of the Park, along established trails.